2009
DOI: 10.1103/physrevlett.102.155002
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Double Layers in Earth’s Plasma Sheet

Abstract: We report the first direct observations of parallel electric fields (E_{ parallel}) carried by double layers (DLs) in the plasma sheet of Earth's magnetosphere. The DL observations, made by the THEMIS spacecraft, have E_{ parallel} signals that are analogous to those reported in the auroral region. DLs are observed during bursty bulk flow events, in the current sheet, and in plasma sheet boundary layer, all during periods of strong magnetic fluctuations. These observations imply that DLs are a universal proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
84
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 21 publications
13
84
0
Order By: Relevance
“…In order to have V eb ∼ 10 8 m/s, the required potential drop across the double layers is DL ∼ 28 kV. Although Andersson et al [2009] do not report observation of double layers in association with the electron holes, but Ergun et al [2009] report strong sequential relation between double layers and electron holes, like that shown in Figure 8b. Figure 1a of Andersson et al [2009] shows intense electron fluxes extending to about 30 keV energy range.…”
Section: Double Layers In Plasma Sheetmentioning
confidence: 86%
See 4 more Smart Citations
“…In order to have V eb ∼ 10 8 m/s, the required potential drop across the double layers is DL ∼ 28 kV. Although Andersson et al [2009] do not report observation of double layers in association with the electron holes, but Ergun et al [2009] report strong sequential relation between double layers and electron holes, like that shown in Figure 8b. Figure 1a of Andersson et al [2009] shows intense electron fluxes extending to about 30 keV energy range.…”
Section: Double Layers In Plasma Sheetmentioning
confidence: 86%
“…When the potential profile is averaged over one ion plasma period, only the ramp containing the multiple double layers is clearly seen at the scale used in Figure 2. However, the instantaneous parallel electric fields at an enlarged horizontal time scale in Figure 8b [60] Andersson et al [2009] have reported data on strong electron hole turbulence observed from THEMIS in the plasma sheet as in the work by Ergun et al [2009]. They find that speed of the electron holes on the average is about 10 8 m/s, faster than the electron thermal velocity V te ∼ 4 × 10 7 km/s.…”
Section: Double Layers In Plasma Sheetmentioning
confidence: 99%
See 3 more Smart Citations